Drug Reaction With Eosinophilia and Systemic Symptoms (DRESS) Syndrome Following Initiation of Sulfasalazine for Ulcerative Colitis: A Yearlong Clinical Challenge - Michael B. Andrews; Michael V. Patrone; Stephen J. Bickston (Case Reports in Gastrointestinal Medicine)
Sulfasalazine, a commonly prescribed medication for treating ulcerative colitis, can cause a severe yet rare adverse drug reaction known as drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome. In this case, a female patient experienced a severe flare of her ulcerative colitis, accompanied by sulfasalazine-induced DRESS syndrome. The ulcerative colitis flare and acute liver injury resolved with a treatment regimen of high-dose steroids and cyclosporine. However, she continued to have treatment-resistant dermatologic changes and delayed organ involvement, including the development of hyperthyroidism that required close multidisciplinary follow-up. IVIG was used to successfully wean steroids and cyclosporine after a year of therapy.